2018
DOI: 10.1002/nbm.3954
|View full text |Cite
|
Sign up to set email alerts
|

In vivo diffusion MRI detects early spinal cord axonal pathology in a mouse model of amyotrophic lateral sclerosis

Abstract: Diffusion magnetic resonance imaging (MRI) exhibits contrast that identifies macro- and microstructural changes in neurodegenerative diseases. Previous studies have shown that MR diffusion tensor imaging (DTI) can observe changes in spinal cord white matter in animals and humans affected with symptomatic amyotrophic lateral sclerosis (ALS). The goal of this preclinical work was to investigate the sensitivity of DTI for the detection of signs of tissue damage before symptoms appear. High-field MRI data were acq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 82 publications
(179 reference statements)
0
17
0
Order By: Relevance
“…Another recent study showed that hippocampal dentate gyrus atrophy predicted pattern separation impairment in patients with LGI1 encephalitis (Hanert et al, 2019). Besides, diffusion tensor imaging (DTI) has been extensively applied to unveil white matter abnormalities in diverse neurological diseases (Gatto et al, 2018;Gatto and Weissmann, 2019). The microstructural integrity impairments of the hippocampus (Finke et al, 2017), corona radiata, capsula interna and corpus callosum (Szots et al, 2017) were found in patients with anti-LGI1 encephalitis in the DTI studies.…”
Section: Introductionmentioning
confidence: 99%
“…Another recent study showed that hippocampal dentate gyrus atrophy predicted pattern separation impairment in patients with LGI1 encephalitis (Hanert et al, 2019). Besides, diffusion tensor imaging (DTI) has been extensively applied to unveil white matter abnormalities in diverse neurological diseases (Gatto et al, 2018;Gatto and Weissmann, 2019). The microstructural integrity impairments of the hippocampus (Finke et al, 2017), corona radiata, capsula interna and corpus callosum (Szots et al, 2017) were found in patients with anti-LGI1 encephalitis in the DTI studies.…”
Section: Introductionmentioning
confidence: 99%
“…This technique has been reported and it will be shown in the future if it will contribute to significantly reduce the recording time. The role of DKI (Marrale et al, 2016 ) has not been generally established yet, although—due to its improved sensitivity to complex microstructural changes—successful studies in TBI (Hansen et al, 2017 ; Soni et al, 2019 ) and early microstructural changes in the ALS brain (Gatto et al, 2018b , c , 2019 ) have already been performed; thus, DKI might be considered to be one of the promising techniques to be included in the data acquisition protocols of future experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Cohort DTI studies have been performed for the SOD1 mouse model of ALS for the spinal cord (Kim et al, 2011 ; Underwood et al, 2011 ; Marcuzzo et al, 2017 ), detecting longitudinal white matter degeneration alongside histology and electron microscopy. DTI of ALS brains of SOD1-mice at 9.4 T and 16.7 T, respectively, have shown a presymptomatic decrease in axonal organization by FA and neurite content by Intracellular Volume Fraction across the spinal cord, corpus callosum, hippocampus, and cortex; the combination of DTI, neurite orientation dispersion, and density imaging (NODDI), and diffusion kurtosis imaging (DKI) (Marrale et al, 2016 ) models have proved to provide an assessment of the early microstructural changes in the ALS brain (Gatto et al, 2018b , c , 2019 ). Longitudinal DTI in the TDP-43 G 298 S ALS mouse model at the cohort level revealed cortical and callosal microstructure alterations (Müller et al, 2019 ); in this study, longitudinal DTI scans at 11.7 T of baseline and follow-up scans with an interval of several months were investigated by voxelwise comparison as well as by tractwise analysis, while histological investigations complemented the in-vivo results.…”
Section: Applications To Models Of Neurodegenerative Diseasesmentioning
confidence: 99%
“…of the control (Fig 3D), but no statistically significant differences (P = 0.2013) were found between the two groups in this subinterval. In the literature, RD changes in SOD1 G93A mice were reported inconsistently [43,[45][46][47]. Hence, further studies on changes of D weights in this subinterval could help to explain the RD inconsistency in DTI measurements and might provide information about fine variations of microenvironment where inflammation, axonal loss, axonal injury, and demyelination coexist.…”
Section: Plos Onementioning
confidence: 97%
“…On the averaged D weight distributions of both groups (Fig 3C), obvious differences were observed in the 7 th , 4 th and 2 nd subintervals between mutant and wild type groups (Table 1). Among them, the 7 th subinterval [1.66×10 −4 ,8.41×10 −4 ] mm 2 /s incorporates the radial diffusivity (RD) of mouse spinal cord (approximately 4.5×10 −4 mm 2 /s) reported in the literature [43,44]. The likely higher S aDw in the mutant mouse existed when comparing to that https://doi.org/10.1371/journal.pone.0231598.g002…”
Section: Plos Onementioning
confidence: 99%